Comparison of diagnostic accuracy of computed tomography virtual endoscopy and flexible fibre-optic laryngoscopy in the evaluation of neck anatomic structures and neoplasms. Issue 1 (February 2021) - Guarnizo, Angela; Glikstein, Rafael; Tsehmaister-Abitbul, Vered; Busca, Ionut; El-Sayed, Samy; Odell, Michael
Background and purpose: Computed tomography virtual endoscopy (CT-VE) is a non-invasive technique which allows visualisation of intraluminal surfaces by tridimensional reconstruction of air/soft tissues. The aim of this study was to compare the diagnostic accuracy of CT-VE and flexible fibre-optic laryngoscopy (FFL) in identifying normal neck anatomic structures and pharyngeal and laryngeal lesions. Methods: Forty-two patients with a history of neck cancer were assessed by two ENT surgeons using FFL and by one neuroradiologist using CT-VE in order to evaluate the visualisation of the epiglottis, vallecula, glossoepiglottic folds, pyriform sinuses, vocal cords and mass pathology. The visualisation of the structures in both modalities was assessed according to the following score: 0 = not visualised, 1 = partial visualisation, 2 = complete and clear visualisation. A weighted kappa coefficient was used to evaluate the inter-observer agreement. McNemar's test was performed to compare the two diagnostic tests. Results: The inter-observer agreement between FFL and CT-VE was fair in the assessment of the vocal cords ( k = 0.341); moderate in the assessment of the glossoepiglottic folds ( k = 0.418), epiglottis ( k = 0.513) and pyriform sinuses ( k = 0.477); and substantial in the assessment of the vallecula ( k = 0.618) and the tumour (0.740). McNemar's test showed no significant difference between the two tests ( p <0.05). Conclusion: CT-VE is a non-invasive technique with a diagnostic accuracy comparable to FFL in terms of visualisation of anatomical structures and pharyngeal and laryngeal lesions.